A review on anaerobic membrane bioreactors (AnMBRs) focused on modelling and control aspects. (December 2018) - Robles, Ángel; Ruano, Maria Victoria; Charfi, Amine; Lesage, Geoffroy; Heran, Marc; Harmand, Jérôme; Seco, Aurora; Steyer, Jean-Philippe; Batstone, Damien J.; Kim, Jeonghwan; Ferrer, José
Highlights: AnMBR needs further research to optimize process efficiency. Modelling can provide insight into the factors playing a key role in AnMBR. Process models still face a long path to adaptation in practice. Better understanding of fouling mechanisms in AnMBRs is required. Control strategies can be further optimized from mechanistic knowledge of fouling. Abstract: The use of anaerobic membrane bioreactor technology (AnMBR) is rapidly expanding. However, depending on the application, AnMBR design and operation is not fully mature, and needs further research to optimize process efficiency and enhance applicability. This paper reviews state-of-the-art of AnMBR focusing on modelling and control aspects. Quantitative environmental and economic evaluation has demonstrated substantial advantages in application of AnMBR to domestic wastewater treatment, but detailed modelling is less mature. While anaerobic process modelling is generally mature, more work is needed on integrated models which include coupling between membrane performance (including fouling) and the biological process. This should include microbial factors, which are important to generation of specific foulants such as soluble and particulate inert organics. Mature and well-established control tools, including better feedback control strategies are also required for both the process, and for fouling control.